Effect of Different Nitrogen Percentage Input On Soil Fertility, Plant Nutrients and Yield of Organic Spinach (Amaranthus Spp.) (Research in Agriculture Livestock and Fisheries, 2022)
Nitrogen (N) management is important to assess the N effect on soil and plant under the organic farming system. With this in mind, a glasshouse experiment was conducted to determine the effect of various N inputs on selected soil chemical properties, nutrient content and yield of spinach (Amaranthus spp). The experimental treatments were focused on the different percentages of N input (2, 4 and 6% of N from organic sources) with soil alone as a control. The treatments were applied 14 days after seeding (14-DAS) at a recommended rate of 2 t/ha. The study result found that 4-6% of N input (with T3 and T4) had improved selected soil parameters such as pH, CEC, total N, available-P and exchangeable-Ca. Further, total N content in spinach (cultivated organically), as well as spinach yield, were significant. Study findings have shown that within 4% to 6% of N input promotes soil quality, total nutrients in spinach (leafy vegetables), and can be scaled up to farm level to sustain organic system productivity.Vol. 9, No. 2, August 2022: 135-144